Thermal-hydraulic characteristics and performance of 3D wavy channel based printed circuit heat exchanger. (5th August 2015) - Khan, Hamid Hassan; M, Aneesh A.; Sharma, Atul; Srivastava, Atul; Chaudhuri, Paritosh
Abstract: CFD study is done here to propose an efficient PCHE (Printed Circuit Heat Exchanger) model; used as a recuperator in International Thermonuclear Experimental Reactor (ITER). 3D steady state conjugate heat-transfer numerical simulations are done; considering the variation of thermo-physical properties as a function of temperature. Helium is used as a working fluid and alloy 617 as solid substrate. The study is done for various angle of bend ( θ  = 0°(straight), 5°, 10° and 15°) and Reynolds number ( Re  = 350, 700, 1400 and 2100). Various types of flow patterns, within one wavy-section, are presented to analyze thermal-hydraulic characteristics. Thermal hydraulic performance parameters are presented for the various wavy-sections as well as within a section; and for the complete PCHE model. Heat transfer enhancement as compared to pressure penalty is higher for the wavy channel; and increases with increasing Re and θ . Wavy as compared to plane channel based PCHE is demonstrated here to give better thermal-hydraulic performance. A detailed characteristics as well as performance-parameters for thermal hydraulics in a 3D wavy channel based PCHE model − not found in the literature − is presented here. Highlights: Studied effect of Reynolds number and angle of bend. Analyzed thermal-hydraulic characteristics, by various types of flow pat-terns. Demonstrated an increase in local heat flux due to change in the flow-direction. Demonstrated better performance of wavy as compared to plane channel based PCHE. Proposed correlation for friction factor and Nusselt number.